ANGIOSPERMIC FLORA OF THE DEMARCATED AMBROSE ALLI UNIVERSITY BOTANICAL GARDEN EKPOMA, EDO STATE, NIGERIA - Ogbevire, Philip; Agholor, A. Iziegbe; Obadoni, Benard O.; Ekpenyong, Adetokunbo; Ogie-Odia, Efosa A.; Imade, Francis N. (FUDMA JOURNAL OF SCIENCES, 2025)
The Ambrose Alli University (AAU) Botanical Garden, Ekpoma, Nigeria, is a defined area established for the conservation of indigenous plant species and the collection, cultivation, maintenance and display of a wide range of plants taxa. Functioning also as a teaching and research facility under the Faculty of Life Sciences, the garden serve critical and conservatory purposes. However, despite its institutional importance and potential utility to conservation biology, the angiospermic diversity of the AAU Botanical Garden has never been systematically documented This study was therefore conducted to provide a comprehensive inventory of the angiospermic flora within the demarcated section of the garden located in Esan West Local Government Area, Edo State. Plant samples were collected using a collapsable quadrant method and identified through standard taxonomic procedure. A total of 91 plant species belonging to 43 families were recorded. These included 36 trees species, 38 shrubs, 10 herb, 6 climbers and 1 grass species. Notably, species such as icacina trihantha (oliv.) and sphenocentrum jollyanum were observed to occur frequently across most quadrats. This study bridged a critical knowledge gap by documenting the angiospermic composition of the AAU Botanical Garden and provide a useful reference for future research, conservation planning and education purposes.
Keywords: Angiospermic flora; Botanical garden; Biodiversity; Conservation; Quadrat sampling